1999
DOI: 10.1074/jbc.274.44.31327
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Kaposi's Sarcoma-associated Herpesvirus G Protein-coupled Receptor Is Necessary for High Affinity Chemokine Binding but Not for Constitutive Activity

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) contains a gene encoding a G protein-coupled receptor (KSHV-GPCR) that is homologous to mammalian chemokine receptors. KSHV-GPCR signals constitutively (in an agonist-independent manner) via the phosphoinositide-inositol 1,4,5-trisphosphate pathway. Because it has been proposed that the N terminus (N-TERM) of other GPCRs may act as tethered agonists, we determined whether the N-TERM of KSHV-GPCR is necessary for constitutive signaling activity or ligand binding, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Through protein engineering of ORF74 a series of pharmacological phenotypes with modulated constitutive activity and/or ligand binding pro®le have been generated, which can be exploited to address this basic question. For example, truncations of the N-terminus of ORF74 eliminates binding of all chemokines, without in¯uencing its high basal activity as presented in Figure 4, upper left box (Ho et al, 1999;. Another interesting phenotype in which the agonist ± but not inverse agonist ± action is eliminated, is obtained by mutating the Arg residues at the extracellular ends of TM-V (Figure 4, upper right box).…”
Section: Orf74 From Hhv8mentioning
confidence: 96%
“…Through protein engineering of ORF74 a series of pharmacological phenotypes with modulated constitutive activity and/or ligand binding pro®le have been generated, which can be exploited to address this basic question. For example, truncations of the N-terminus of ORF74 eliminates binding of all chemokines, without in¯uencing its high basal activity as presented in Figure 4, upper left box (Ho et al, 1999;. Another interesting phenotype in which the agonist ± but not inverse agonist ± action is eliminated, is obtained by mutating the Arg residues at the extracellular ends of TM-V (Figure 4, upper right box).…”
Section: Orf74 From Hhv8mentioning
confidence: 96%
“…In order to obtain clonal transfectants, selected neomycin plates were split to obtain isolated colonies. The clones and pools (containing multiple clones) were screened for KSHV-GPCR expression by measuring specific binding with radiolabeled growth-related oncogene ␣ (Gro␣), a ligand for KSHV-GPCR (15,16), and receptor signaling through the inositol phosphate (InsP) pathway. One pool and one clone expressing KSHV-GPCRs (MLEC/KSHV-GPCR), and one pool transfected with empty plasmid (MLEC/mock) were chosen for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…It seems, however, that the ability of the inverse agonists to inhibit signaling by these receptors was inversely related to the level of constitutive activity of the receptor. Other KSHV-GPCR mutants have been found to be unresponsive to inverse agonist inhibition but these were receptors with mutations in their amino-terminal domains that caused loss of binding (10,11).…”
Section: Viral G Protein-coupled Receptor Activationmentioning
confidence: 99%
“…In a previous report (10), we tested the hypothesis that the amino-terminal extracellular domain of KSHV-GPCR may serve as a "tethered ligand" that constitutively activates the receptor. Although we found that the amino terminus was important for high affinity binding of chemokines, we showed that the amino terminus was not important for constitutive signaling.…”
mentioning
confidence: 99%